STUDIES ON DIVERSITY AND DYNAMICS OF CLADOCERA IN A SUB TROPICAL SUNGAL POND, AKHNOOR (J AND K) - K. K. SHARMA; SANJAY KOTWAL (The Bioscan, 2011)
Sungal pond on Akhnoor–Sohal road was selected for the present study which involved the physico-chemical examination of the pond along with analysis of diversity and dynamics of Cladoceran from November 2009 to October 2010. A total 8 (eight) species of cladocera belonging to 6 (six) genera and 4 (four) families were recorded which enjoyed well marked seasonal dynamics in the population during the present investigation.